Sudden and unexpected deaths in adults : an investigation of cases reported to Tygerberg Forensic Pathology Services from January 2001 - December 2005 - Tiemensma, Marianne (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MMed (Pathology. Forensic Medicine))--University of Stellenbosch, 2010.